Antimicrobial Susceptibility Profiles of Commensal Staphylococcus spp. Isolates from Chickens in Hungarian Poultry Farms Between 2022 and 2023 - Ábel Szabó; Ákos Jerzsele; László Kovács; Ádám Kerek (Antibiotics)
Background: Antimicrobial resistance is one of the greatest challenges of our time, urging researchers in both veterinary and public health to engage in collaborative efforts, thereby fostering the One Health approach. Infections caused by Staphylococcus species can not only lead to significant diseases in poultry but also pose serious threats to human life, particularly in hospital (nosocomial) infections; therefore, it is crucial to identify their antimicrobial resistance. Methods: Our objective was to assess the susceptibility profile of commensal Staphylococcus aureus strains (n = 227) found in commercial chicken flocks in Hungary through the determination of minimum inhibitory concentration (MIC) values. Results: Based on our findings, resistance to tiamulin (82.8%; 95% CI: 77.4–87.2%) and doxycycline (74.4%; 95% CI: 68.5–79.7%) is the most critical. The 55.1% (95% CI: 48.8–61.3%) resistance rate to enrofloxacin, a critically important antimicrobial, is also concerning. The fact that 58.6% (95% CI: 52.4–64.5%) of the strains were resistant to amoxicillin and 35.7% (95% CI: 29.7–42.1) were resistant to amoxicillin–clavulanic acid suggests that a proportion of the strains produce β-lactamase. Comparing our results with the available human hospital data, it was found that resistance to macrolide antibiotics is similarly high in both cases. Conclusions: Our findings highlight the necessity of conducting regular surveillance studies, which would allow the monitoring of future temporal trends. This information could benefit practitioners making clinical decisions to successfully treat infections. To uncover the underlying causes of multidrug resistance, next-generation sequencing can be employed to elucidate the genetic basis of phenotypic resistance.